The use of Breast Milk Fortifier in Preterm Infants by paediatric dietitians in the UK. Issue 1 (2nd November 2020) - Jupe, Sophie; Maslin, Kate
Abstract: Background: Breast milk is the feed of choice for premature infants, although its nutritional composition is not always sufficient to meet their raised nutritional requirements. The addition of a multi‐nutrient breast milk fortifier (BMF) to breastmilk is recommended; however, international guidelines on the use of BMF are inconsistent. The present study aimed to explore the use of BMF in preterm infants by paediatric dietitians in the UK. Methods: A questionnaire was designed and sent to members of the British Dietetic Association neonatal specialist group ( n = 100) using a secure online platform. Descriptive statistics were calculated. Results: Forty dietitians completed the survey, all of whom used BMF. Local hospital BMF guidelines were available to 77.5% ( n = 31). The most commonly used criteria for commencing BMF were: tolerating a feed volume of 150 mL kg −1 day −1 (72.5%, n = 29), a gestational age <34 weeks (67.5%, n = 27) and a birth weight <1500 g (60%, n = 24). The primary contraindication for the use of BMF was necrotising enterocolitis (NEC). The majority of respondents used standard fortification, with individualised fortification available to only 12.5% ( n = 5). The most common indicators for discontinuing BMF were on discharge home (67.5%, n = 27), satisfactory growth (65%, n = 26) or feeding directly from the breast (62.5%, n = 25). Conclusions: Although BMF is used more proactively in UK neonatal units than previously, variation in practice remains. Individualised fortification is very uncommon and caution remains regarding risk of NEC. The development of national guidelines on the use of BMF would help to standardise nutritional care in neonatal units. Abstract : The present study aimed to explore the use of breast milk fortifier in preterm infants by paediatric dietitians in the UK. In a survey of 40 dietitians, we found that breast milk fortifier is used more proactively than before; however, variation in practice remains. Individualised fortification is very uncommon and caution remains regarding the risk of necrotising enterocolitis.